SUPPLY CHAIN MANAGEMENT OF AGRO INDUSTRY OF CASSAVA - Timisela, Natelda Rosaldiah; Leatemia, Ester D.; Polnaya, Febby J.; Breemer, Rachel (Universitas Brawijaya, Indonesia, 2017)
The purpose of this study was to determine the mechanism of supply chain and the pattern of cassava of agroindustry supply chain flow and analyze the relationship between the components of SCM and the impact on supply chain activity improvement and agroindustry performance. Sample of research were producers of agroindustry local food of cassava as much of 106 respondents were taken by simple random sampling. The data analyzed by qualitative and quantitative analysis. Qualitative analysis used to describe the mechanism and pattern of cassava of agroindustry supply chain flow and principles of SCM. While quantitative analysis used to analyze the components, SCM activity improvement and agroindustry performance by using a structural equation model. The results showed that the mechanism of cassava agroindustry supply chain is the creation of collaboration and coordination among supply chain actors ranging from farmer, processor, distributor and consumer. Structural equation modeling analysis results showed the expected value to meet the criteria and are very good although AGFI marginally acceptable or good enough as an index measuring GFI (0.900), AGFI (0.860), TLI (.974), CFI (0.980), Cmin/DF (1.147 ), RMSEA (0.038), the probability (0.204) and the value of c2 (68.813).